1987
DOI: 10.1111/j.1432-1033.1987.tb13656.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte heterogeneity in response to extracellular ATP

Abstract: 1. The metabolic and hemodynamic effects of extracellular ATP in perfused rat liver were compared during physiologically antegrade (portal to hepatic vein) and retrograde (hepatic to portal vein) perfusion. ATP in concentrations up to 100 pM was completely hydrolyzed during a single liver passage regardless of the perfusion direction.2. The ATP(20 pM)-induced increases of glucose output, perfusion pressure and ammonium ion release seen during antegrade perfusions were diminished by 85 -95% when the perfusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
(8 reference statements)
2
46
1
Order By: Relevance
“…The data indicate a preferential inactivation of icosanoids in the perivenous region of the acinus, near the outflow of the sinusoidal bed, whereas their site of action is more upstream. The data are in line with a hypothesis that a major function of a perivenous cell population near the outflow of the sinusoidal bed ('perivenous scavenger cells') is to inactivate or eliminate a variety of potentially toxic compounds which escaped periportal disposal, including ammonia, which escaped periportal urea synthesis [34]), extracellular nucleotides [35] and icosanoids.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The data indicate a preferential inactivation of icosanoids in the perivenous region of the acinus, near the outflow of the sinusoidal bed, whereas their site of action is more upstream. The data are in line with a hypothesis that a major function of a perivenous cell population near the outflow of the sinusoidal bed ('perivenous scavenger cells') is to inactivate or eliminate a variety of potentially toxic compounds which escaped periportal disposal, including ammonia, which escaped periportal urea synthesis [34]), extracellular nucleotides [35] and icosanoids.…”
supporting
confidence: 62%
“…The temperature was 37 "C. Perfusions were carried out either in the antegrade (portal to caval vein) or the retrograde (caval to portal vein) direction. Changes of the perfusion direction in the individual perfusion experiment occurred within 3 -5 s and were performed as described previously [34,35]. The perfusion flow was 3.2-4.5 ml min-' (g liver)-' and was constant within 5% throughout the individual experiment and also after repeated changes of the perfusion direction.…”
Section: Hemoglobin-free Liver Perfusionmentioning
confidence: 99%
“…The inactivation of C3a by the liver might play an important role in its self-protection during systemic generation of the anaphylatoxin. The cells at the entrance of the sinusoids might act as protecting scavengers as proposed previously [24]. Thus, it seems unlikely that C3a generated systemically in the circulation has an effect on liver metabolism or hemodynamics.…”
Section: Function Of the Metabolic And Hemodynamicmentioning
confidence: 73%
“…KA values (agonist concentrations at which half maximal activation is obtained) have been computed as described previously [3,[13][14][15] These data do not however exclude an in vivo occurrence of zonation of hormonal glycogenolysis. Indeed, using a perfused system, H~iussinger et al [16] reported on liver heterogeneity in response to extracellular ATP, the periportal area being more responsive to ATP than the perivenous hepatocytes. These data are not necessarily in contradiction with our findings showing no different glycogenolytic capacity between hepatocytes originating from the two zones.…”
Section: Resultsmentioning
confidence: 99%